Toleransi Agama Menurut Pandangan Syaikh Wahbah Al-Zahayli - Alaika Abdi Muhammad (IAIN Tulungagung, 2020)
Abstract Religious tolerance has always been an interesting topic of study. The relations between religions in various parts of the world make the study has an important position. Many religious leaders try to explain the meaning of tolerance based on the verses of the Koran. The contemporary scholar who gives serious attention to tolerance is Wahbah al-Zuhayli. Methodologically, his interpretation tends to follow the approach of classical Ulema scholars. The problem of tolerance that he explained is based on the current social reality of religious communities. The idea of tolerance offered by al-Zuhayli begins with an explanation of the concept of wasatiyyah al-Islam. Furthermore, the interpretation of al-Zuhayli's tolerance has four main points: First, the union of Islam with the Abrahamic Religion. The existence of several roots of the same teachings in Abrahamic Religion is a way to form a moderate and tolerant attitude. Second, the principle of freedom in choosing a religion. Third, the prohibition of spreading hatred and terror. Fourth, the recommendations prioritizing justice. Al-Zuhayli's interpretation revealed a pattern of harmonious and tolerant relations between religious communities. This is, at the same time, a scientific criticism of the doctrines of violence that are echoed by radical groups. Keywords: Religious tolerance, Wahbah al-Zuhayli, Wasathiyyah al-Islam (Islamic moderations). Abstrak Tema toleransi agama selalu menjadi topik yang menarik untuk dikaji. Pasangsurut hubungan antar umat beragama di berbagai belahan dunia, tak terkecuali di Indonesia, membuat kajian ini memiliki posisi yang penting dalam studi agama. Banyak agamawan, khususnya para ulama tafsir yang bersaha menjelaskan makna toleransi secara normatif berdasarkan ayat-ayat Al-Qurán. Ulama kontemporer yang memberi perhatian serius tentang toleransi adalah Wahbah al-Zuhayli. Meski secara metolodolgis penafsiran al-Zuhayli cenderung mengikuti pendekatan nas ulama klasik. Namun, problem toleransi yang ia jelaskan berdasarkan realitas sosial umat beragama saat ini. Gagasan toleransi yang ditawarkan oleh al-Zuhayli diawali dengan penjelasannya tentang konsep wasatiyyah al-Islam (moderasi Islam). Selanjutnya, al-Zuhayli mengelompokan empat hal pokok tema toleransi yang dijelaskan al-Qur’an. Pertama, relasi antar Agama Samawi. Adanya beberapa akar ajaran yang sama dalam agama samawi merupakan jalan untuk membentuk sikap moderat dan toleran. Kedua, asas kebebasaan dalam memilih agama. Poin ini menegaskan prinsip Ri’ayah al-Din yang diusung syari’at Islam. Ketiga, larangan menebar kebencian. Dan ke-empat Larangan tindakan teror serta anjuran mengutamakan keadilan. Setiap manusia berhak mendapatkan perlindungan atas kemerdekaan jiwanya. Penafsiran al-Zuhayli mengungkap adanya pola hubungan harmonis dan toleran antar umat beragama. Hal ini sekaligus merupakan kritik ilmiah atas doktrin-doktrin kekerasan yang sering dikumandangkan kelompok radikal. Kata Kunci: Toleransi agama, Wahbah al-Zuhayli, Wasathiyyah al-Islam (moderasi Islam).